Web-based information system of Malaysian's Chinese recipe (e-Recipes) / Yeoh Chen Chen - Yeoh, Chen Chen (2001)
With the tremendous growth of the World Wide Web, more and more information is being put on the Internet. No matter what type of information, it is including the field of education, business, news and entertainment. The Internet creates an information-rich environment of various resources, which can be obtained any time and from any place. E-Recipes is an information system Web site that provides and promotes Malaysian's Chinese Recipe and other relevant information to the eyes of people all around the world. The main objective of this project is to develop an attractive, dynamic interactive, in formative and user-friendly online recipe Web site using FrontPage 2000 and Macromedia Dreamweaver 3. A standard interface across Web pages will be adopted to give a pleasant and easy learning to browse the site. The development of E-Recipes emphasized to be a browser and platform independent. This was accomplished by using both of JavaScript and VBScript to code the client side processing in order to support a wider range of type of Web browsers while Active Server Pages was choosing to code the server side processing respectively. Internet Information Server 4.0 (HS) that runs on Windows NT server platform was chosen in this project as the Web server. It is aimed to have a high-performance back-end database that is MS Access for providing recipe information.